The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7150/ijbs.41653
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Nitric Oxide Collaborated with Radiotherapy to Promote Anti-Tumor Immune Response via Inducing CD8+ T Cell Infiltration

Abstract: The production of nitric oxide (NO) is a key feature of immunosuppressive myeloid cells, which impair T cell activation and proliferation via reversibly blocking interleukin-2 receptor signaling. NO is mainly produced from L-arginine by inducible NO synthase (iNOS). Moreover, L-arginine is an essential element for T cell proliferation and behaviors. Impaired T cell function further inhibits anti-tumor immunity and promotes tumor progression. Previous studies indicated that radiotherapy activated anti-tumor imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Increased ROS drives MDSCs immunosuppressive activity on T-cells as well as inhibit its differentiation to other myeloid cells [39]. Elevated level of ROS is a major characteristic of MDSCs present in tumor-bearing mice and cancer patients [40][41][42]. The immune-suppressive function of MDSCs in tumorbearing mice and cancer patients can be overcome by blocking ROS production in MDSCs [43].…”
Section: Discussionmentioning
confidence: 99%
“…Increased ROS drives MDSCs immunosuppressive activity on T-cells as well as inhibit its differentiation to other myeloid cells [39]. Elevated level of ROS is a major characteristic of MDSCs present in tumor-bearing mice and cancer patients [40][41][42]. The immune-suppressive function of MDSCs in tumorbearing mice and cancer patients can be overcome by blocking ROS production in MDSCs [43].…”
Section: Discussionmentioning
confidence: 99%
“…In human malignancies, iNOS co-expression with COX-2 is often observed [ 7 , 17 ]. On the other hand, NO has been shown to impede cellular immunity, and iNOS inhibitors improve efficiency of immunotherapy and radiotherapy in mice by enhancing T and NK cell infiltration and activity [ [18] , [19] , [20] , [21] ]. The specific role of NO activity on macrophages, major drivers of tumour-associated inflammation, remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of WT mice with the iNOS inhibitor 1400W, which leads to a specific inhibition of NO produced by M 58 , led to decreased percentages of both peroxynitrite + LT-HSC and apoptotic LT-HSC and to a better recovery of LT-HSC number 21 days post-TBI. A 1400W treatment combined with radiotherapy increases survival and delays or suppresses tumor growth in pancreas, lung and breast cancer 59,60 . Our results strengthened its use in cancer treatment as we showed that 1400W treatment also protected LT-HSC from potential deleterious effects of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%